2011
DOI: 10.1246/cl.2011.292
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Triplet States of Photoconductive TTF Derivatives Including a Fluorescent Group

Abstract: The spin dynamics of photoconductive tetrathiafulvalene (TTF) derivatives containing 2,5-diphenyl-1,3,4-oxadiazole (PPD) was examined using time-resolved electron spin resonance (TR-ESR) spectroscopy. TR-ESR signals of a frozen solution sample under visible excitation were attributed to the excited triplet state T1, which was populated via intersystem crossing from the excited singlet state S1 as confirmed by TR-ESR spectral simulations. From DFT calculations, the spin-density distribution of the T1 state was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…During the first stage of photo-induced electron transfer, a charge-separate (CS) state composed of a radical cation of the donor (D •+ ) and a radical anion of the acceptor (A •-) could be generated; therefore, an ESR-based method would be a strong investigative tool for this process. 165,166 Time-resolved ESR (TR-ESR), 167 one of the established ESR methods, can probe the radical pair generated by a laser flash, which may provide insight into the dynamics of the primary process. This method was applied to the photoinduced electron transfer process in a donor-acceptor covalent organic framework (COF) consisting of zinc phthalocyanine (ZnPc) and naphthalene diimide (NDI) as the electron donor and acceptor, respectively (Fig.…”
Section: Time-resolved Esr As a Probe Of Charge Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the first stage of photo-induced electron transfer, a charge-separate (CS) state composed of a radical cation of the donor (D •+ ) and a radical anion of the acceptor (A •-) could be generated; therefore, an ESR-based method would be a strong investigative tool for this process. 165,166 Time-resolved ESR (TR-ESR), 167 one of the established ESR methods, can probe the radical pair generated by a laser flash, which may provide insight into the dynamics of the primary process. This method was applied to the photoinduced electron transfer process in a donor-acceptor covalent organic framework (COF) consisting of zinc phthalocyanine (ZnPc) and naphthalene diimide (NDI) as the electron donor and acceptor, respectively (Fig.…”
Section: Time-resolved Esr As a Probe Of Charge Dynamicsmentioning
confidence: 99%
“…During the first stage of photo-induced electron transfer, a charge-separate (CS) state composed of a radical cation of the donor (D + ) and a radical anion of the acceptor (A À ) could be generated; therefore, an ESR-based method would be a strong investigative tool for this process. 165,166 Time-resolved ESR (TR-ESR), 167 one of the established ESR methods, can probe the radical pair generated by a laser flash, which may provide insight into the dynamics of the primary process.…”
Section: Time-resolved Esr As a Probe Of Charge Dynamicsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Several TTF-C 60 dyads have been investigated as photofunctional materials because the C 60 moiety shows fast charge separation and slow charge combination in the photoinduced excited state that are preferable for the application to solar cells. [15][16][17] On the other hand, to investigate photoinduced conducting crystalline materials, we have also studied crystal structures and electrochemical, optical and conducting properties of several TTF-based D-A dyads combined with fluorescent molecules such as 2,5-diphenyl-1,3,4-oxadiazole (PPD), 18,19 1,3-benzothiazole (BTA), 20,21 and 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY), 22 because these fluorescent parts have planar p-electron frameworks that are indispensable for the formation of effective p-stacking columnar structures, considering the difficulty in the cases of TTF dyads containing a bulky C 60 molecule. We have reported photocurrent generation based on single crystalline samples of these D-A dyads, and found that preferable p-stacking structures of the TTF moieties and formation of photoinduced charge-separated states between the TTF moieties and fluorescent parts are quite important factors influencing photoconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported photocurrent generation based on single crystalline samples of these D-A dyads, and found that preferable p-stacking structures of the TTF moieties and formation of photoinduced charge-separated states between the TTF moieties and fluorescent parts are quite important factors influencing photoconductivity. 19 Among them, we recently focused on fluorene derivatives because fluorene is well-known as a strongly fluorescent p-electron framework in the fields of polymer-based electroluminescent materials and solar cells, [23][24][25][26] and D-A dyads containing TTF and 2,5,7-trinitrofluorene derivatives showed interesting charge-transfer interactions. 27,28 We used fluorene as an antenna for photoexcitation as in the cases of porphyrins combined with fluorenyl pendants 29,30 because of its highly fluorescent character and high planarity.…”
Section: Introductionmentioning
confidence: 99%
“…Organometallic compounds of TTF derivatives [7][8][9], which connects π-and d-electron systems directly, are also expected to exhibit stronger exchange interaction. TTF derivatives connected with photoactive π-acceptors also give photoconductive materials [10,11].…”
mentioning
confidence: 99%